THE LEGAL POSITION OF ILLEGITIMATE CHILDREN ACCORDING TO THE REGULATIONS THAT WERE IN FORCE IN THE TERRITORY OF VOJVODINA IN THE KINGDOM OF SERBS, CROATS AND SLOVENES - Drakić, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In the Kingdom of Serbs, Croats and Slovenes existed six different legal territories. Legal particularism that existed in the common state of Serbs, Croats and Slovenes was one of the major problems in state that caused many problems in the everyday life of citizens. One of the main goals of the authorities was to execute equating of laws. Special shortened procedure for equating of laws was established by the St. Vitus’ Day Constitution. In the territory of Vojvodina mainly were valid Hungarian laws. Illegitimate children were in a inferior legal postion than children born in wedlock according to the laws that were in force in the territory of Vojvodina. Illegitimate child was in kinship only with its mother. Non-marital children could be equated with children born in wedlock in two cases prescribed by law: if parents of illegitimate child enter marriage later on, or pursuant to the Royal Decree. The legal position of non-marital children was one of the outstanding social issues in the state that had to be uniformly resolved.
Keywords: Hungarian laws; territory of Vojvodina; equating of laws; legal particularism; Kingdom of Serbs; Croats and Slovenes; illegitimate children